2012
DOI: 10.1534/genetics.111.138040
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ypa1 and ypa2, the Schizosaccharomyces pombe Orthologs of the Peptidyl Proyl Isomerases That Activate PP2A, Reveals a Role for Ypa2p in the Regulation of Cytokinesis

Abstract: The Schizosaccharomyces pombe septation initiation network (SIN) regulates cytokinesis. Cdc7p is the first kinase in the core SIN; we have screened genetically for SIN regulators by isolating cold-sensitive suppressors of cdc7-24. Our screen yielded a mutant in SPAC1782.05, one of the two fission yeast orthologs of mammalian phosphotyrosyl phosphatase activator. We have characterized this gene and its ortholog SPAC4F10.04, which we have named ypa2 and ypa1, respectively. We find that Ypa2p is the major form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 115 publications
(163 reference statements)
5
23
0
Order By: Relevance
“…The failure of cdc14-118 to form spores is consistent with the requirement for its partner Sid1p in spore formation (Krapp et al, 2006), and the results for spg1, cdc11 and sid4 confirm those of earlier studies (Krapp et al, 2006;Yan et al, 2008). The ability of sid2-250 to form spores has been documented and explained previously (see Introduction), but it was surprising to find that mob1-R4 and cdc7-24 formed spores, because these mutant proteins are inactive in vegetative cells at 32˚C (Goyal and Simanis, 2012). This not due to a partial suppression of these alleles by pat1-114, because a similar result was observed for diploids of cdc7-24, cdc7-A20 and mob1-R4 in a pat1 + background (data not shown).…”
Section: Requirement For Sin Proteins During Spore Formationsupporting
confidence: 86%
“…The failure of cdc14-118 to form spores is consistent with the requirement for its partner Sid1p in spore formation (Krapp et al, 2006), and the results for spg1, cdc11 and sid4 confirm those of earlier studies (Krapp et al, 2006;Yan et al, 2008). The ability of sid2-250 to form spores has been documented and explained previously (see Introduction), but it was surprising to find that mob1-R4 and cdc7-24 formed spores, because these mutant proteins are inactive in vegetative cells at 32˚C (Goyal and Simanis, 2012). This not due to a partial suppression of these alleles by pat1-114, because a similar result was observed for diploids of cdc7-24, cdc7-A20 and mob1-R4 in a pat1 + background (data not shown).…”
Section: Requirement For Sin Proteins During Spore Formationsupporting
confidence: 86%
“…6F). This indicates that the proposed feedback loop promoting SIN protein asymmetry in anaphase does not require Sid2p to phosphorylate (Goyal and Simanis, 2012). Mutation of the PP2A B9 subunit par1 rescues some SIN mutants (Jiang and Hallberg, 2001;Le Goff et al, 2001).…”
Section: Symmetric Spb Association Of Mob1p-gfp In Early Mitosis Requmentioning
confidence: 94%
“…Previous studies have shown that mutation of the regulatory B subunit Pab1p does not affect the appearance of Cdc7p-GFP at one SPB in anaphase (Lahoz et al, 2010), suggesting that that PP2A-Par1p is involved in promoting the asymmetry of Cdc7p-GFP in anaphase. Previous studies have implicated other PP2A complexes and regulators in promoting the asymmetry of Cdc7p (Goyal and Simanis, 2012;Singh et al, 2011).…”
Section: What Regulates the Early-late Transition?mentioning
confidence: 99%
See 1 more Smart Citation
“…These include the phosphatase complex PP2A (Goyal and Simanis, 2012;Jiang and Hallberg, 2001;Lahoz et al, 2010;Le Goff et al, 2001), Clp1p Trautmann et al, 2001), calcineurin (also known as PP2B) (Lu et al, 2002) and the PP2A-related SIN-inhibitory phosphatase (SIP) complex (Singh et al, 2011), which is the counterpart of the mammalian striatin interacting phosphatase and kinase (STRIPAK) complexes (Hwang and Pallas, 2014). Loss of calcineurin or Clp1p function is deleterious in SIN mutant backgrounds, suggesting that they promote SIN signalling.…”
Section: Regulators Of Sin Signalling Protein Phosphatasesmentioning
confidence: 99%